Traditional Ambivalence and Heterosexual Marriage in Canada: Transgressing Ritual or Ritualising Transgression? - Greenhill, Pauline; Armstrong, Angela (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2006)
Queer moments abound in traditional rituals associated with marriages and weddings, not only in some regions of English Canada but in most European and European-colonised locations. In the Prairie provinces and Ontario, mock weddings (folk dramatic travesties of the Christian/majoritarian wedding ceremony, usually performed cross dressed) can interrupt wedding showers or milestone anniversary parties. And from Prince Edward Island to British Columbia, charivaris (late night visits to a newly married couple, featuring extreme noisemaking and/or traditional trickery) can follow a marriage. The authors question whether these practices transgress against conventional heterosexual marriage or merely ritualise and thus contain potential resistance to its strictures, and find that they do both.